Cardiopulmonary effects of apneustic anesthesia ventilation in anesthetized pigs: a new mode of ventilation for anesthetized veterinary species - Bukoski, Alex; Downs, John; Hodgson, David S.; Le-Bert, Carolina R.; Thomen, Robert; Flors, Lucia; Thombs, Lori; Bailey, James (Frontiers in Veterinary Science, 2024)
Objective: To compare the cardiopulmonary effects of apneustic anesthesia ventilation (AAV) and conventional mechanical ventilation (CMV) in anesthetized pigs and to describe a new mode of ventilation for anesthetized veterinary species. Study Design: Randomized, crossover design without washout. Twelve healthy, female white Landrace pigs. Methods: Following ketamine-midazolam premedication and anesthetic induction with propofol, the trachea was intubated, and each pig was positioned in dorsal recumbency. Anesthesia was maintained with propofol and sufentanil infusions. Pigs were instrumented and their lungs were sequentially ventilated with each mode, in random order, for 1 hour according to predefined criteria [fraction of inspired oxygen (FIO2) = 0.21, 10 mL kg-1 tidal volume (VT), and arterial carbon dioxide tension (PaCO2) within 40-45 mmHg]. Cardiopulmonary data were collected at baseline, 30 and 60 minutes. In 8 pigs, thoracic computed tomography (CT) was performed following the 60-minute time point for each mode of ventilation and images were analyzed to quantify lung aeration. The effects of ventilation mode, time, and order were analyzed using repeated measures ANOVA. Paired t-tests were used to compare lung aeration between modes. Significance was defined as p < 0.05. Results: Data from 12 pigs were analyzed. A significant effect of mode was found for heart rate, mean arterial pressure (MAP), pulmonary artery occlusion pressure, cardiac index (CI), stroke volume index, systemic vascular resistance, pulmonary vascular resistance, oxygen delivery index (DO2I), oxygen extraction ratio (O2ER), VT, arterial oxygen tension, arterial hemoglobin saturation, PaCO2, end-tidal CO2 tension, alveolar dead space (VDalv/VTalv), venous admixture (𝑄𝑠/𝑄𝑡), mean airway pressure, and dynamic compliance index (CRSI). Order effects were observed for some cardiovascular and respiratory variables. Thoracic CT of 8 pigs revealed that AAV resulted in larger proportions of normally and hyperaerated lung while CMV resulted in larger proportions of hypoaerated and atelectatic lung. In dorsally recumbent anesthetized pigs, ventilated with FIO2 = 0.21, both modes of ventilation supported adequate oxygenation while AAV resulted in higher CRSI, and lower VDalv/VTalv and 𝑄𝑠/𝑄t, compared with CMV. AAV was also associated with lower MAP, CI, and DO2I and higher O2ER compared with CMV. Further investigation of AAV in anesthetized animals is warranted.